Social work research in practice : ethical and political contexts - D'Cruz, Heather; Jones, Martyn (SAGE Publications, 2014)
This new edition of Social Work Research: Ethical and Political Contexts explores the intrinsic connection between knowledge, research and practice in social work. The authors argue that through a better appreciation of research, the highest standards of social work can be achieved. The second edition investigates contemporary approaches which impact on the discourses of social work research, including: - Evidence-based practice - User-led research - Anti-oppressive practice - Practice-based research Each chapter has been fully updated with a rich range of case examples and references. Further reading is also included, so that readers can expand their knowledge. This book is a valuable resource for both undergraduate and postgraduate students, as well as practitioners working in the field of social work